Wittgenstein's Theory of Metaphysical Expression and Meaning : Analytical Research - Nala Fareed Ibrahim; Hassan Hussein (QALAAI ZANIST JOURNAL, 2022)
The problem of metaphysics is one of the philosophical issues of the current era, especially for the analytic philosopher (Ludwig Wittgenstein), who clearly defends phrases with meanings against phrases without meanings in his book (Tractatus) . Metaphysical expressions are one of the issue that Wittgenstein considered as a reason for the absence of an analogue and images of its components in the external world, describing it as meaningless and at the same time describing it as without sign and significance. An attempt was made to resolve this problem through a logical analysis of language and expressions, so that the phrase with meaning is the one of that is subject to conjugation and has an analogy in the external world and speaks directly about facts and phenomena within this world , otherwise all expressions are meaningless if these conditions are not met. At the same time , the values of correctness and error of expressions were linked to their ability to conjugate .Any expression and expression that is not subject to recognition of its value as true or false is unscientific and falls outside the meaning. Metaphysical expressions do not meet this condition, so they are considered meaningless and without reference.